Energy-Dependent Chirality Effects in Quasifree-Standing Graphene - Dombrowski, Daniela; Jolie, Wouter; Petrović, Marin; Runte, Sven; Craes, Fabian; Klinkhammer, Jürgen; Kralj, Marko; Lazić, Predrag; Sela, Eran; Busse, Carsten (Physical review letters, 2017)
We present direct experimental evidence of broken chirality in graphene by analyzing electron scattering processes at energies ranging from the linear (Dirac-like) to the strongly trigonally warped region. Furthermore, we are able to measure the energy of the van Hove singularity at the M point of the conduction band. Our data show a very good agreement with theoretical calculations for free-standing graphene. We identify a new intravalley scattering channel activated in case of a strongly trigonally warped constant energy contour, which is not suppressed by chirality. Finally, we compare our experimental findings with T-matrix simulations with and without the presence of a pseudomagnetic field and suggest that higher order electron hopping effects are a key factor in breaking the chirality near to the van Hove singularity.